A Normative Dataset of the Balance Error Scoring System in Children Aged Between 5 and 14. Issue 6 (November 2016) - Hansen, Colby; Cushman, Dan; Anderson, Nicholas; Chen, Wei; Cheng, Christine; Hon, Shirley D.; Hung, Man
Abstract : Objective: Pediatric head injuries occur commonly and are being reported in increasing numbers. Balance testing is a key component in the evaluation of suspected concussion, and the balance error scoring system (BESS) is likely the most well-known and widely used measure. To date, normative BESS scores for adults have been reported but not for children. Design: Normative data for BESS scores and modified BESS scores were created in a cohort of healthy children. Potential variables were analyzed as predictors of BESS performance. Setting: Local elementary and junior high schools. Participants: A total of 373 healthy children between the ages of 5 and 14. Interventions: The BESS was performed on all children. Assessment of Risk Factors: Gender, body mass index percentile, previous concussions, athletic participation, age, and the parental opinion of child's balance ability were examined as factors associated with the BESS score. Main Outcome Measures: BESS scores. Results: Normative data are reported, stratified by age groups of 5 to 7 years, 8 to 10 years, and 11 to 14 years of age, for both BESS and modified BESS. Median BESS scores are 23 for children aged 5 to 7, 18 for children aged 8 to 10, and 16 for children aged 11 to 14. Median modified BESS scores are 8 for children age 5 to 7, 5 for children age 8 to 10, and 4 for children age 11 to 14. Increasing age and positive parental opinion regarding their child's balance ability were independently correlated with decreasing BESS scores ( P < 0.01). Conclusions: The normative data on BESS scores for healthy children reported here provide age-stratified reference values for suspected balance alterations.